Motor learning in rats: modification of the pattern of reaching and licking by operant conditioning - Hernandez-Mesa, N; Mamedov, Z; Bures, J (Physiologia Bohemoslovaca, 1985)
Motor learning was studied in computer controlled experiments in which the prolongation of a definite phase of a discrete movement was reinforced by intracranial selfstimulation or by the offer of water. In Experiment 1, rats slowed down the retraction phase of the lateralized reaching reaction from 300 ms to 512 ms. In Experiment 2, rats learned to follow computer generated spout movement by increasing the interlick interval or by alternating long and short licks.
Keywords: krysa rodu Rattus; Animals; Behavior, Animal; Conditioning, Operant; Movement; Reinforcement, Psychology; posilování (psychologie); chování zvířat; mužské pohlaví; zvířata; Male; pohyb; Rats; operantní podmiňování